IMPLEMENTASI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN PADA PERSEROAN TERBATAS (PT) FRUIT LAND (STUDI KASUS ALL FRESH FRUIT STORE DAERAH TB SIMATUPANG JAKARTA SELATAN TAHUN 2022). - Azriel Hanafi, (2023)
This study aims to describe how the implementation of the Employment Social Security Agency (BPJS) at the All Fresh Fruit Store in the TB Simatupang area, South Jakarta. The method used in this research is descriptive qualitative by relying on primary and secondary data sources. Data collection is done through observation, interviews, and documentation. To analyze the research results, the theory of policy implementation according to George C. Edward III is used as an analytical knife, by focusing on communication, resources, attitudes of implementers, and bureaucratic structures. The results of the study show that the implementation of the Employment BPJS program at the All Fresh Fruit Store in the TB Simatupang area in 2022 has experienced several obstacles and has not gone well. The findings highlight several problems, including the non-availability of the Employment BPJS program by some employees due to the poor relationship between management and employees. In addition, not all employees at the All Fresh Fruit Store in the TB Simatupang area receive the BPJS Employment program, which creates gaps in social protection for workers. In conclusion, this study provides an overview of the challenges and implementation of the BPJS Employment program at the All Fresh Fruit Store in the TB Simatupang area, Jakarta South in 2022.